Analisis Beberapa Faktor Yang Mempengaruhi Produktivitas Kerja Pengrajin Patung Kayu Di Desa Mas Dan Desa Peliatan Kecamatan Ubud - I Made Wyasa Sedhanaputra (Universitas 17 Agustus 1945 Semarang, 2023)
This study aims to analyze several factors that influence the work productivity of wood sculpture craftsmen in Mas and Peliatan Village, Ubud District, namely wages, work experience, and working capital, either simultaneously or partially. The data in this study all use primary data obtained by distributing questionnaires to the 77 respondents who were sampled. Determination of the sample is determined by accidental sampling technique. The analysis technique used is multiple linear regression analysis. The results of the study show that the variables of wages, work experience, and working capital simultaneously have a significant effect on the income of the informal sector angkringan businesses in Denpasar City. Partially the variables of wages, work experience, and working capital have a positive and significant effect on the work productivity of wooden sculpture craftsmen in Mas Village and Peliatan Village, Ubud District.